2023
DOI: 10.32607/actanaturae.11708
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for Cystic Fibrosis: recent advances and future prospects

Maria A. Lomunova,
Pavel M. Gershovich

Abstract: Gene replacement therapies are novel therapeutic approaches that seek to tackle hereditary diseases caused by a congenital deficiency in a particular gene, when a functional copy of a gene can be delivered to the cells and tissues using various delivery systems. To do this, viral particles carrying a functional copy of the gene of interest and various nonviral gene delivery systems, including liposomes, nanoparticles, etc., can be used. In this review, we discuss the state of current knowledge regarding the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…This includes pulmonary disease monitoring with lung function tests, radiological imaging and sputum evaluations; gastroenterologic evaluation for malabsorption and obstruction syndromes; endocrinologic screening for DM; ENT evaluation for nasal polyposis and sinusitis; musculoskeletal evaluation for any muscular or bone abnormality, including bone density scans, etc. The treatment of CF patients includes targeted mucoactive agents and physiotherapy support for airway clearance; targeted antibiotic and immunomodulatory therapy via various forms and routes for prevention and treatment of recurrent infections, dietary support, targeted exercise, and gene therapies; 54 , 55 and other specific treatments targeted to various complications to which CF patients might succumb. 56 Detailed report of the treatment and monitoring of CF patients is beyond the limits of this article.…”
Section: Cf: Disease Monitoring and Managementmentioning
confidence: 99%
“…This includes pulmonary disease monitoring with lung function tests, radiological imaging and sputum evaluations; gastroenterologic evaluation for malabsorption and obstruction syndromes; endocrinologic screening for DM; ENT evaluation for nasal polyposis and sinusitis; musculoskeletal evaluation for any muscular or bone abnormality, including bone density scans, etc. The treatment of CF patients includes targeted mucoactive agents and physiotherapy support for airway clearance; targeted antibiotic and immunomodulatory therapy via various forms and routes for prevention and treatment of recurrent infections, dietary support, targeted exercise, and gene therapies; 54 , 55 and other specific treatments targeted to various complications to which CF patients might succumb. 56 Detailed report of the treatment and monitoring of CF patients is beyond the limits of this article.…”
Section: Cf: Disease Monitoring and Managementmentioning
confidence: 99%
“…The discovery of drugs that can modulate CFTRs and rectify the functioning of the defective protein have had positive impact on the life expectancy, quality of life, and given hope to many CF patients. Nonetheless, about 10% of patients are unresponsive to CFTR modulators because CFTR is not synthesized at all or is only synthesized in low quantities [55]. In addition, clinical trials (CT) show that 10% -20% of CF patients have individual intolerance to modulator drugs [56].…”
Section: Gene Therapy Approaches For Cystic Fibrosismentioning
confidence: 99%
“…Following the failure of the first-generation Ad vectors, Scientist began the search for alternative approaches in gene delivery to target cells. The reports from the CTs using the AAV2 vector to deliver the CFTR gene showed that introduction of the vector into the lungs of CF patients did not cause significant side-effects, but the efficacy was disappointing, since none of the CTs demonstrated significant CFTR expression or correction of pathological CF manifestations [55]. This failure can be attributed to the following reasons; insufficient efficacy of gene insertion due to the inability of viral particles to penetrate the thick secretion layer in the airways, insufficient promoter strength in the expression cassette, or immune response of the host to the introduction of the viral vector [71].…”
Section: Adeno-associated Viral (Aav) Vectors As Gene Delivery Agentmentioning
confidence: 99%
See 1 more Smart Citation